EVALUASI NILAI JEMBATAN PRA DAN PASCA ERUPSI MERAPI 2010 MENGGUNAKAN SIMULASI ALTERNATIF RUTE DITINJAU DARI ASPEK EKONOMI DAN ASPEK SOSIAL Studi Kasus : Jembatan Pagerjurang, Bulaksalak, Salam dan Geblok di Kecamatan Cangkringan - , Dedhi Noviandy, Arief Setiawan Budi Nugroho, ST., M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The bridge is an important component in a network of roads. Bridges are the infrastructure connecting inter - isolated areas by rivers, hills, seas, etc. For that reason, the existence of the bridge is essential in order to maintain economic and social life of the society. If a bridge is broken, then it can automatically interrupt the economic and social life of the society. This research was a bridge evaluation method using route alternative simulation in order to find out bridge functional value reviewed from economic and social aspects. The object of the research was Pagerjurang, Bulaksalak, Salam, and Kulon Geblok bridges which crossed from North to South over Opak River. Meanwhile, variables affecting bridge value were distance between village center point to reference point, types of pavement, village economic potency, and population of the villagers. All villages were reviewed towards a reference point